Elastic Laminal Invasion in Colon Cancer: Diagnostic Utility and Histological Features - Kojima, Motohiro; Yokota, Mitsuru; Saito, Norio; Nomura, Shogo; Ochiai, Atsushi (Frontiers in Oncology, 2012)
Primary tumors of the colorectal cancers are assessed pathologically based on the tumor spread into the bowel wall. The assessment of serosal involvement, which may be relevant to pT4, can be challenging for pathologists, making the consistency of diagnoses questionable. As solutions to this problem, the following two strategies could be adopted. One would be to use special staining or immunohistochemical staining techniques for diagnostic assistance. The other would be to construct recommendations for the assessment of tumor spreading and to obtain a world-wide consensus on the criteria used to assess tumor spreading. Using elastic staining, we previously reported that peritoneal elastic laminal invasion (ELI) could be objectively determined and would likely contribute to a simplified and more objective stratification of deep tumor invasion around the peritoneal surface. We also noted the importance of sampling, staining, and histo-anatomical knowledge in the application of elastic staining during routine pathological diagnosis. Here we review the history of primary tumor stratification leading to the present TNM classification and report on the current status of pathological assessments made at our hospital to summarize what has been established and what is further required for the pathological diagnosis of tumor spreading in patients with colorectal cancer.